Tenure Insecurity, Gender, Low-Cost Land Certification and Land Rental Market Participation in Ethiopia - Holden, Stein T.; Deininger, Klaus; Ghebru, Hosaena (2012)
There is a renewed interest in whether land reforms can contribute to market development and poverty reduction in Africa. This paper assesses effects on the allocative efficiency of the land rental market of the low-cost approach to land registration and certification of restricted property rights that was implemented in Ethiopia in the late 1990s. Four rounds of a balanced household panel from 16 villages in northern Ethiopia are analysed, showing that land certification initially enhanced land rental market participation of (potential) tenant and landlord households, especially those that are headed by females.